PENDUGAAN POTENSI HUTAN SAGU DENGAN MENGGUNAKAN TEKNIK PENGINDERAAN JAUH - Ishak Sumantri Haryono (Jurnal Penelitian Hasil Hutan, 1988)
The aim of this study is to apply remote sensing techniques to estimate sago potential.   The estimation  method  of sago potential  is a linear regression equation. Estimate  parameter from  aerial photo  scale of  1: 20000 is the crown  density  as dependent  variable  while sago soft  core (empulur)   volume as the in dependent  variable.                                                                                            .                                         The linear regression equation  of the sago potential  is Ŷ =  3.6731 X  +  147.43 with 0. 7313 coefficient  corelation.  Based  on the study  the linear regression equation  above appear to have reliable estimate  and proved  to be useful for  planning  of sago forest  management.